2013
DOI: 10.12927/hcpol.2013.23467
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Health Information Technology Adoption and Family Physicians’ Practice Patterns in Canada: Evidence from 2007 and 2010 National Physician Surveys

Abstract: The Robert Wood Johnson Foundation focuses on the pressing health and health care issues facing our country. As the nation's largest philanthropy devoted exclusively to improving the health and health care of all Americans, the Foundation works with a diverse group of organizations and individuals to identify solutions and achieve comprehensive, meaningful and timely change. For more than 35 years the Foundation has brought experience, commitment, and a rigorous, balanced approach to the problems that affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…This can be a particular problem for patients with complex health problems, including chronic diseases or comorbidities, who may need additional time to have their health issues addressed [14]. Whereas many previous studies focused on the determinants of the workload of GPs (see for example [15][16][17][18][19][20][21][22][23]), studies on the consequences of high workload in GPs for patient experiences are sparse. Previous studies showed that extended consultation length is related to increased patients' ability to cope with their illness and life in general [24], and more positive experiences with the care provided by GPs [25].…”
Section: Introductionmentioning
confidence: 99%
“…This can be a particular problem for patients with complex health problems, including chronic diseases or comorbidities, who may need additional time to have their health issues addressed [14]. Whereas many previous studies focused on the determinants of the workload of GPs (see for example [15][16][17][18][19][20][21][22][23]), studies on the consequences of high workload in GPs for patient experiences are sparse. Previous studies showed that extended consultation length is related to increased patients' ability to cope with their illness and life in general [24], and more positive experiences with the care provided by GPs [25].…”
Section: Introductionmentioning
confidence: 99%
“…The typical primary care provider in Canada sees 20-25 patients in a day, many with complex problems (Sarma, Hajizadeh, Thind, & Chan, 2013). The average length of a primary care provider visit in Canada is approximately 15 minutes during which time the average patient will discuss more than three health concerns in 37% of visits (Sarma et al, 2013). This implies that primary care providers including NPs and family physicians have little time to address health promotion along with other medical issues.…”
Section: Primary Care and Health Promotionmentioning
confidence: 99%